PENGETAHUAN DAN SIKAP TENTANG TUBERKULOSIS PARU DENGAN PERILAKU PENCEGAHAN TUBERKULOSIS PARU MASYARAKAT UMBULHARJO YOGYAKARTA - Adefi Putri Manunggal; Hariza Adnani (STIKes Surya Global Yogyakarta, 2016)
Background: Tuberculosis (TB) is still a public health problem in the world, especially in countries - developing countries including Indonesia.Disease is a major threat to the development of human resources that require the attention of all parties.In fact, the current number of TB patients in Indonesia was ranked fourth highest in the world.Indonesia ranked fourth highest for patients with TB after China, India, and South Africa.Results of a preliminary study conducted at the City Health Office Yogyakarta in 2014 Puskesmas Umbulhajo I ranks first with 72 TB patients, for 2015 at the health center I Umbulharjo most TB patients are in Sub Sorosutan.Objective: Toexamine the correlation between knowledge and attitude of pulmonary tuberculosis with lung tuberculosis prevention behavior in the community in the Village Sorosutan city of Yogyakarta in 2016. Methods: This research is non experiment with this type of analysis quantitative descriptive and cross-sectional study design.The sampling technique used is proportional sampling as many as 100 respondents.The analysis used are univariate and bivariateResults:Kendall Tau analysis showed no association knowledge sig.=0.033 and attitude sig.=0.013 and p-value less than α (0.05). Conclusion: From this study we can conclude that knowledge with attitudes related to preventive behaviors in the community in the village of Umbulharjo Sorosuran Yogyakarta 2016 Keywords: Attitude and Behavior Prevention, Knowledge